Cultura de segurança do paciente e esgotamento em profissionais da saúde de um Hospital Universitário de Manaus: estudo transversal - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The culture of patient safety indicates the commitment of healthcare organizations to the safety. Individual factors such as satisfaction and professional burnout are related to the safety culture and may impact the care provided at the hospital. Objective: to assess culture of patient safety and burnout at the work among a university hospital's professionals. Method: This is a cross-sectional study with random sampling and calculation of the sample size in 300 employees. The data were collected in electronic devices containing the tools Safety Attitudes Questionnaire, Maslach Burnout Inventory Human Service Survey and sociodemographic variables. Data were analyzed using the Stata 14.2 software to calculate frequencies, associated factors and reliability by Cronbach's alpha. Results: 323 were invited to reach 300 respondents (response rate = 92.9%); 67.3% were women, mean age 42 years ± 10.85, 41.3% of the nursing area and 84.0% with direct contact with patients. The mean positivity in the safety culture was 62.7% (α=0.920). The domain with the best perception of safety culture was job satisfaction (81.4%), while working conditions showed the least positivity (46.5%). Professionals who work in direct contact with patients (β=7.03, p=0.021), workers with three or more employment contracts (β=5.80, p=0.026) and with a workday exceeding 60 hours weekly (β=6.57; p=0.014) presented greater perception of safety culture. The prevalence of burnout among professionals was 8.7% (95% confidence interval [CI]: 5.2-12.3%, α = 0.908), 26.3% presented severe burnout in professional accomplishment, 23% in emotional exhaustion and 19.7% in depersonalization. Burnout was less frequent among employees aged 36-50 years (PR=0.43, 95% CI: 0.19-0.98), with partner (PR=0.36, 95% CI: 0.18-75), economic class B2 (mean middle class, PR=0.28, 95% CI: 0.11-0.75) and C/D/E (lower middle class/poor/extremely poor, PR=0.11, 95% CI: 0.01-0.80) and nurses (PR=0.35, 95% CI: 0.14-0.91). Singles presented more burnout (PR=2.34, 95% CI: 1.10-4.98) when compared to married. Conclusion: The safety culture showed weaknesses, especially in relation to working conditions. Approximately 1 in 10 employees presented burnout, which was higher in singles, younger and richer.
Keywords: Segurança do paciente; Esgotamento profissional; Pessoal de saúde; Profissional da Saúde; CIÊNCIAS DA SAÚDE: FARMÁCIA